MEDIA PEMBELAJARAN INTERAKTIF UNTUK ANAK SEKOLAH MINGGU PADA GKE SINTA PARARAPAK - Nugroho, Bayu Pratama; Hendartie, Susi; Dwinanti, Rosalia (STMIK Palangkaraya, 2021)
Sunday School is an activity to teach children the basics of Christianity by delivering material according to the contents of the Bible, including the introduction of Christian songs that are packaged in a simple manner so that they are easy to understand. However, in learning activities, the teacher's way of conveying messages in the Bible is by telling stories. The learning process is conventional and has limited teaching aids and takes a long time to convey the material. In this study, the method of collecting observation data, interviews, references, documentation and questionnaires was used, while the system development method used MDLC, and the design used UML. The final result of this research is interactive learning media for Sunday school children that can be used by children for Christian religious activities. Based on the results of the user response to interactive learning media for Sunday school children by 80.4%